2020
DOI: 10.1101/2020.08.27.20182808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Potential Role of Extracellular Vesicles in COVID-19 Associated Endothelial injury and Pro-inflammation

Abstract: COVID-19 infection caused by the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has resulted in a global pandemic with the number of deaths growing exponentially. Early evidence points to significant endothelial dysfunction, micro-thromboses, pro-inflammation as well as a dysregulated immune response in the pathogenesis of this disease. In this study, we analyzed the cargo of EVs isolated from the plasma of patients with COVID-19 for the identification of potential biomarkers of disease sev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 37 publications
(47 reference statements)
2
35
0
Order By: Relevance
“… 42 Fourth, in extracellular vesicles, significantly higher levels of S100A12 were observed in patients with severe versus moderate COVID-19. 43 Fifth, higher levels of S100A8/A9 and a distinct DAMP RAGE ligand, HMGB1, were found to associate with higher risk of intensive care unit admission and death in patients with COVID-19. 44 Sixth, HMGB1 was reported to induce NETosis (neutrophil extracellular traps) 45 and to induce ACE2 expression, critical for SARS-CoV-2 entry into cells.…”
Section: Rage—from Its Discovery In the Endothelium And Onwardsmentioning
confidence: 97%
“… 42 Fourth, in extracellular vesicles, significantly higher levels of S100A12 were observed in patients with severe versus moderate COVID-19. 43 Fifth, higher levels of S100A8/A9 and a distinct DAMP RAGE ligand, HMGB1, were found to associate with higher risk of intensive care unit admission and death in patients with COVID-19. 44 Sixth, HMGB1 was reported to induce NETosis (neutrophil extracellular traps) 45 and to induce ACE2 expression, critical for SARS-CoV-2 entry into cells.…”
Section: Rage—from Its Discovery In the Endothelium And Onwardsmentioning
confidence: 97%
“…Endothelial EVs are particles naturally released from ECs contained by a lipid bilayer and carry coding and noncoding RNA, proteins, DNA fragments, and lipids, which facilitate cell–cell communication ( 12 , 13 ). An increased number of endothelial EVs has been reported in a variety of vascularly related disorders ( 14 , 15 ), and their amounts inversely correlated with endothelial function ( 11 ).…”
Section: Potential Biomarkers In Covid-19mentioning
confidence: 99%
“…An increased number of endothelial EVs has been reported in a variety of vascularly related disorders ( 14 , 15 ), and their amounts inversely correlated with endothelial function ( 11 ). A recent study reported that EVs isolated from the plasma of patients with COVID-19 carried high concentration of proinflammatory cytokines, proteases, and peptidases, which correlated with disease severity ( 12 ). This suggests that EVs could be important players in COVID-19 pathophysiology and disease progression.…”
Section: Potential Biomarkers In Covid-19mentioning
confidence: 99%
“…More recently, Cappellano and collaborators reported that platelet EVs, quantified by CD31 and CD41 flow cytometry on 2 independent cohorts in Italy, were significantly elevated in hospitalized patients, as compared to healthy controls. Importantly, a proteomics profiling study of large EVs isolated from 53 hospitalized COVID-19 patients in China, found that alterations in pro-inflammatory, coagulation, and endothelial injury protein cargo in the large EVs may contribute to severe COVID-19 (30). On the other hand, Yu and collaborators reported that pseudotyped SARS-CoV-2 and HIV-based lentivirus induces the production of EVs with adaptive immunity-like antiviral functions in murine hypothalamic neural stem cells (31).…”
Section: Extracellular Vesicles In Covid-19 Patientsmentioning
confidence: 99%